External influences on ecological theory: report on organized oral session 80 at the 100th anniversary meeting of the ecological society of America - Huston, Michael A.; Ellison, Aaron M.; Frank, David; Jackson, Stephen T.; Jiang, Xichen; Lau, Matthew; Lockwood, Jeffrey A.; Prager, Steven D.; Reiners, Derek S.; Reiners, William A.; Schulze, Ernst-Detlef; Vandermeer, John H.; et al. (Wiley, 2016)
The 100-year history of the Ecological Society of America spans most of the major advances in the field of ecology, from the “niche” of Grinnell and others, to Lotka and Volterra's models of predation and competition based on the logistic growth equation, to the concept of competitive exclusion developed from experimental ecology, to genetics and evolutionary ecology and all the ramifications and specializations of these topics over the rest of the 20th and into the 21st century.